Antibacterial activity of bovine milk lactoferrin and its hydrolysates prepared with pepsin, chymosin and microbial rennet against foodborne pathogen Listeria monocytogenes. (June 2015) - Ripolles, D.; Harouna, S.; Parrón, J.A.; Calvo, M.; Pérez, M.D.; Carramiñana, J.J.; Sánchez, L.
Abstract: Lactoferrin is an iron binding glycoprotein that contains antimicrobial peptides in its structure, which are released when hydrolysed by proteases. The antibacterial activity of bovine lactoferrin, its hydrolysates obtained with pepsin, chymosin and microbial rennet, and bovine whey fractions, has been assayed against Listeria monocytogenes serovar 4b in this study. The hydrolysates obtained with each enzyme were found to be inhibitory of bacterial growth; although the activity was lower than that exerted by the whole lactoferrin, except at low concentrations for chymosin and microbial rennet hydrolysates. The antibacterial activity of all the hydrolysates corresponded to the fraction with a molecular mass higher than 3 kDa. The peptides of hydrolysates were fractionated by using sulfonic acid derivatives and the cationic peptides analysed by matrix-assisted laser desorption ionisation-time of flight mass spectrometry. Moreover, some antibacterial activity was found in fractions obtained from bovine whey by size exclusion chromatography.